Genetic characterization of spotted fever group rickettsiae in questing ixodid ticks collected in Israel and environmental risk factors for their infection. Issue 8 (23rd March 2017) - ROSE, JESSICA; NACHUM-BIALA, YAARIT; MUMCUOGLU, KOSTA Y.; ALKHAMIS, MOH A.; BEN-NUN, ADI; LENSKY, ITAMAR; KLEMENT, EYAL; NASEREDDIN, ABEDELMAJEED; ABDEEN, ZIAD A.; HARRUS, SHIMON
SUMMARY: This study aimed to genetically characterize spotted fever group rickettsiae (SFGR) in questing ixodid ticks from Israel and to identify risk factors associated with SFGR-positive ticks using molecular techniques and geographic information systems (GIS) analysis. 1039 ticks from the genus Rhipicephalus were collected during 2014. 109/1039 (10·49%) carried SFGR-DNA of either Rickettsia massiliae (95), ' Candidatus Rickettsia barbariae' (8) or Rickettsia conorii (6). Higher prevalence of SFGR was found in Rhipicephalus turanicus (18·00%) compared with Rhipicephalus sanguineus sensu lato (3·22%). Rickettsia massiliae was the most commonly detected species and the most widely disseminated throughout Israel (87·15% of all Rickettsia -positive ticks). GIS analysis revealed that Central and Northern coastal regions are at high risk for SFGR. The presence of ticks was significantly associated with normalized difference vegetation index and temperature variation over the course of the year. The presence of rickettsiae was significantly associated with brown type soils, higher land surface temperature and higher precipitation. The latter parameters may contribute to infection of the tick with SFGR. Health care professionals should be aware of the possible exposure of local communities and travellers to R. massillae . Molecular and geographical information can help professionals to identify areas that are susceptible to SFGR-infected ticks.